2018
DOI: 10.1177/1559325817751525
|View full text |Cite
|
Sign up to set email alerts
|

PCB118-Induced Cell Proliferation Mediated by Oxidative Stress and MAPK Signaling Pathway in HELF Cells

Abstract: The present study used human lung fibroblast (HELF) cells as a test model to evaluate the role of oxidative stress (OS) and extracellular signal-regulated kinases 1/2 (ERK1/2) protein in HELF cell proliferation exposed to PCB118. Results from 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide demonstrated that PCB118 at lower concentrations stimulated proliferation of HELF cell and abrogate proliferative effect at higher dose concentrations and in a time-dependent manner. Moreover, reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In another study, the cardiovascular mortality dosedependent association for dietary PCB exposure had a hazard ratio (HR) of 1.31 (CI 95%: 1.08 to 1.57; p trend 0.005) [30]. Han et al [3] found significantly positive associations between PCBs (including 81,105,114,118,123,126,156,157,167,169,189,28,52,101,138,153,180,209,202,205,and 208) and the risk of type 2 diabetes, and PCBs showed a linear dose-response relationship with diabetes. These findings indicate that exposure to PCBs may be a diabetogenic factor.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study, the cardiovascular mortality dosedependent association for dietary PCB exposure had a hazard ratio (HR) of 1.31 (CI 95%: 1.08 to 1.57; p trend 0.005) [30]. Han et al [3] found significantly positive associations between PCBs (including 81,105,114,118,123,126,156,157,167,169,189,28,52,101,138,153,180,209,202,205,and 208) and the risk of type 2 diabetes, and PCBs showed a linear dose-response relationship with diabetes. These findings indicate that exposure to PCBs may be a diabetogenic factor.…”
Section: Discussionmentioning
confidence: 96%
“…A long-term inflammatory response, oxidative stress, and release of ROS, as well as activation of subsequent NLRP3 inflammasome signaling, are significantly involved in the pathogenesis of diabetes [ 19 , 24 ]. Studies have shown that PCB118 can increase the production of ROS, induce oxidative stress, and activate the NLRP3 inflammasome [ 25 , 27 , 28 ]. Our study was conducted to explore the potential role and mechanisms of PCB118 and ROS-NLRP3 inflammasome signaling in the inflammation of islet beta cells and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our study in that the excessive generation of ROS could result in a decline in cell function and cause progressive cell damage [ 24 , 25 ]. Moreover, oxidative stress was connected with inhibiting cell proliferation, and hydrogen peroxide (H 2 O 2 ) treatment was able to suppress cell proliferation [ 26 , 27 ]. This evidence suggests the occurrence of hypoxia-induced proliferation inhibition of the mammary gland via impairing its antioxidant system.…”
Section: Discussionmentioning
confidence: 99%